PROVERB AS AN OBJECT OF LINGUISTIC RESEARCH (World Bulletin of Social Sciences, 2024)
These proverbs are the object of constant study by linguists and historians, ethnographers from many fields of linguistics . Proverbs are an important studied object of text linguistics as a semantically and structurally complete text. Grammatically, proverbs are sentences that are considered a specific syntactic unit
Keywords: proverb; linguistic; alliteration; assonance